On the mechanism of photodriven hydrogenations of N 2 and other substrates by Hantzsch ester: Buffer is key to reactive H-atom donors - Christian M. Johansen; Elisabetta Benazzi; Jonas C. Peters (Proceedings of the National Academy of Sciences, 2025)
The Hantzsch ester (HEH 2 ) has found considerable utility as a photoreductant in synthesis, with photodriven transfer hydrogenation reactions typically limited to activated substrates. We recently established that the addition of an organic buffer of collidinium triflate [(ColH)OTf] and collidine (Col) allows photodriven transfer hydrogenation from HEH 2 to N 2 forming NH 3 (nitrogen reduction; N 2 R) in the presence of a Mo catalyst. Given the requirements for Mo-catalyzed thermally driven N 2 R, this result suggested the generation of a significant driving force for proton-coupled electron transfer (PCET) when irradiating HEH 2 in the presence of Col-buffer. In this study, we probe how Col-buffer enables efficient photodriven proton-coupled reductions with HEH 2 . Wavelength-dependent NH 3 yields are consistent with HEH 2 photoexcitation, and the combination of HEH 2 with Col-buffer is privileged. Data are presented, suggesting that HEH 2 is statically quenched via ET to [ColH]OTf through an H-bonded association complex to release ColH • and [HEH 2 ] •+ . Transient absorbance data and EPR studies establish that the resulting [HEH 2 ] •+ intermediate is rapidly deprotonated by Col to yield HEH • , in net furnishing HEH • and ColH • as potent H-atom donors. Broader utility of this reagent combination is demonstrated in the photoreduction of a range of C=O and N=O π-bonds by HEH 2 , with a significant boost in rates and yield, and altered reactivity, observed on addition of Col-buffer. ColH • is posited as the most potent PCET donor generated (BDFE N−H of 28 kcal mol −1 ).